2021
DOI: 10.1016/j.ijscr.2021.105867
|View full text |Cite
|
Sign up to set email alerts
|

Are gastric metastases of renal cell carcinoma really rare? A case report and systematic review of the literature

Abstract: Highlights Solitary gastric metastasis of RCC are scarce. When feasible, surgical or endoscopic treatment of gastric metastasis should be performed. Risk of metastatic recurrence is significant and must be taken into consideration in the therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Compared with metachronous gastric metastasis, patients with synchronous gastric metastasis had shorter median survival, suggesting a poor prognosis. Our data were in consistent with that reported in several other studies [21,24,51,85,86] from different countries where it was reported that the median interval range was 6.3 to 8.5 years and the median survival was 19 months. It can be seen that the time to gastric metastasis of RCC was long after treatment of the primary tumor.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compared with metachronous gastric metastasis, patients with synchronous gastric metastasis had shorter median survival, suggesting a poor prognosis. Our data were in consistent with that reported in several other studies [21,24,51,85,86] from different countries where it was reported that the median interval range was 6.3 to 8.5 years and the median survival was 19 months. It can be seen that the time to gastric metastasis of RCC was long after treatment of the primary tumor.…”
Section: Discussionsupporting
confidence: 93%
“…e optimal treatment for RCC patients with gastric metastasis remains unclear, and the treatment measures taken are different according to the status of gastric metastasis. Endoscopic or surgical treatment can be used for single and early gastric metastasis [24]. Immunotherapy and/or targeted therapy can be used for multiple focal metastases or other organ metastases to improve patient survival [87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As supported in the literature, surgical treatment remains the best therapeutic option for a solitary gastric metastasis. Many studies have even shown that median patient survival was higher after surgical treatment of gastric metastasis in the case of solitary and multiple metastatic sites [ 14 ]. Palliative gastrectomy should be an option for decreased burden on patients and the healthcare system as was for our patient.…”
Section: Discussionmentioning
confidence: 99%
“…The median time duration between the diagnosis of clear cell renal cell carcinoma and metachronous gastric metastasis has been reported to be 8.5 years. 7 Such a long time interval may decrease the clinical suspicion of metastatic disease and make the diagnosis even more challenging. Most of the cases with gastric metastasis are identified in autopsy studies or diagnosed by endoscopy.…”
mentioning
confidence: 99%